Feasibility of Social Distancing Practices in US Schools to Reduce Influenza Transmission During a Pandemic. Issue 4 (July 2020) - Uscher-Pines, Lori; Schwartz, Heather L.; Ahmed, Faruque; Zheteyeva, Yenlik; Tamargo Leschitz, Jennifer; Pillemer, Francesca; Faherty, Laura; Uzicanin, Amra
Abstract : Background: Schools are socially dense environments, and school-based outbreaks often predate and fuel community-wide transmission of seasonal and pandemic influenza. While preemptive school closures can effectively reduce influenza transmission, they are disruptive and currently recommended only for pandemics. We assessed the feasibility of implementing other social distancing practices in K-12 schools as a first step in seeking an alternative to preemptive school closures. Methods: We conducted 36 focus groups with education and public health officials across the United States. We identified and characterized themes and compared feasibility of practices by primary versus secondary school and region of the United States. Results: Participants discussed 29 school practices (25 within-school practices implemented as part of the school day and 4 reduced-schedule practices that impact school hours). Participants reported that elementary schools commonly implement several within-school practices as part of routine operations such as homeroom stay, restriction of hall movement, and staggering of recess times. Because of routine implementation and limited use of individualized schedules within elementary schools, within-school practices were generally felt to be more feasible for elementary schools than secondary schools. Of reduced-schedule practices, shortening the school week and the school day was considered the most feasible; however, reduced-schedule practices were generally perceived to be less feasible than within-school practices for all grade levels. Conclusions: Our findings suggest that schools have many options to increase social distance other than closing. Future research should evaluate which of these seemingly feasible practices are effective in reducing influenza transmission in schools and surrounding communities.